Two Dimensional Modeling of III-V Heterojunction Gate All Around Tunnel Field Effect Transistor - Manjula Vijh; R.S. Gupta; Sujata Pandey (Журнал нано- та електронної фізики)
Tunnel Field Effect Transistor is one of the extensively researched semiconductor devices, which has captured attention over the conventional Metal Oxide Semiconductor Field Effect Transistor. This device, due to its varied advantages, is considered in applications where devices are scaled down to deep sub-micron level. Like MOSFETs, many geometries of TFETs have been studied and analyzed in the past few years. This work, presents a two dimensional analytical model for a III-V Heterojunction Surrounding Gate Tunneling Field Effect Transistor. 2-D Poisson’s equation in cylindrical coordinates has been solved to derive the expression of Surface Potential and threshold voltage of the device. A broken gap GaSb/InAs heterostructure has been considered in this work. Variation of potential profiles are shown with different gate and drain biases, by varying radius of the transistor,and different gate metals. Also, variation of threshold voltage is shown with respect to channel length and radius of the nanowire.